Adaptation of Promising Rice Genotypes for Broadcast Aus Season (Bangladesh Rice Journal, 2020)
Rice cultivation in Aus season is eco-friendly and essential for sustainable food security of Bangladesh utilizing rain water rather than extracting underground water. Four rice genotypes (BR6855-3B-12, BR6855-3B-13, BR6848-3B-12 and BR6976-2B-11-1) along with check variety BRRI dhan43 were evaluated at farmers’ field during broadcast Aus season. The objectives were to investigate the adaptability of the rice genotypes and find out promising genotype(s) for Broadcast Aus rice. The experiment was conducted at farmers’ field in eight agro-ecological zones of Bangladesh. Randomized complete block design (RCB) was used with three replications. Standard and uniform management practices were followed for all the locations. Data were taken on grain yield, days to 80% maturity, plant height, panicles m-2, 1000-grain weight, grains panicle-1, spikelet sterility (%), Phenotypic acceptance at vegetative and maturity stage, pest incidence; feedback of farmers and extension personnel. Genotypes, environments and interaction of genotypes by environments had significant effect on grain yield, yield components and agronomic parameters. Analysis of variance indicated that there were significant differences between the check (control) and improved genotypes except the genotype BR6976-2B-11-1 which was similar with the check BRRI dhan43 for all parameters. Correlation analysis was also performed to establish extent of association between yield and major yield components. Grain yield positively and significantly correlated with the agronomic parameters except spikelet sterility. Across the locations, BR6848-3B-12 produced significantly the highest grain yield (4.88 t ha-1) at Feni while the lowest grain yield (1.58 t ha-1) was obtained in BR6976-2B-11-1 followed by BRRI dhan43 (1.64 t ha-1) at Kushtia. BR6848-3B-12 showed yield advantage of 1.0 t ha-1 over the check variety BRRI dhan43 with similar growth duration (104 day). AMMI stability value, yield stability index and GGE Bi-plot model indicated that BR6855-3B-12 is the most adaptable, suitable and stable genotype for broadcast Aus rice across the locations, and finally it is released in 2017 as BRRI dhan83 for broadcast Aus season.Bangladesh Rice j. 2019, 23(2): 35-48